THE USE OF TECHNOLOGY IN DISTANCE LEARNING IN ELEMENTARY SCHOOLS: A POST-PANDEMIC LITERATURE ANALYSIS - Devi Melani; Rayi Anissai Rahma Puti Zahro (SMART: Journal of Multidisciplinary Educational, 2025)
This study aims to analyze the use of technology in distance and blended learning in Indonesian elementary schools during the post-pandemic era, focusing on teacher readiness, infrastructure availability, student engagement, and home learning support. Employing a literature review method, this research systematically synthesizes studies published between 2020 and 2025 from Scopus, Google Scholar, and national academic repositories. The findings reveal significant disparities between urban and remote schools regarding digital literacy, internet stability, and access to learning devices. Urban schools demonstrate higher levels of teacher training, stable connectivity, and stronger parental support, resulting in higher student engagement and improved learning outcomes. Conversely, rural and remote schools struggle with limited infrastructure, inadequate teacher digital competence, and low parental involvement, which negatively affect learning quality. The novelty of this research lies in its integrative framework combining technology readiness, pedagogical adaptation, and socio-contextual equity at the elementary education level—a focus that remains underexplored in post-pandemic digital learning studies. Furthermore, the study contributes globally by highlighting how developing countries can transform emergency remote learning into sustainable hybrid models aligned with inclusive education principles. It concludes that successful implementation of distance learning in primary education requires holistic coordination between teachers, infrastructure providers, families, and policymakers. These findings provide valuable insights for educators and policymakers to design equitable, technology-driven learning systems capable of sustaining education quality in both urban and remote settings.